A Tool to Support Model-Based Testing Activities - Doi Junior, Gilson; Bonifacio, Adilson (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2011: Anais do I Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2011)
The occurrence of fault on embedded critical systems can result in financial damage and human losses, as well. Rigorous approaches based on formalisms, specially testing routines, have been proposed to guarantee more reliable systems. Model-based testing is a rigorous approach to support testing activities, e.g. test case generation. Theoretical results have been validated in the literature, but there are few tools to support practical applications. Thus, we develop a tool to support practical experiments which allows us to make a comparison among model-based test case generation methods by pointing more suitable sceneries for each one.